Utilizing satellite remote sensing and GIS techniques for air quality monitoring / Rohayu Haron Narashid - Haron Narashid, Rohayu (2005)
Air quality monitoring is needed to control air pollution in urban areas. A limited number of air quality monitoring stations, limits the initial strategy of pollution prevention program in Malaysia in air quality monitoring especially at micro-scale level. The technique used to monitor air quality involves manual measurement of pollution concentrations within the area of measuring station. A more practical approach is needed to study air quality at micro-scale. One possibility is the use of satellite remote sensing and Geographical Information System (GIS) technologies. The aim of this study is to evaluate the suitability of satellite remote sensing and GIS techniques for air quality monitoring. Three (3) different LANDSAT 7 Enhance Thematic Mapper Plus (ETM+) datasets dated the 15th of July 2000, 31st of May 2001 and 20th of September 2001 and eight (8 ) Continuous Air Quality Monitoring (CAQM) data are used to determine the relationship between digital number (DN) of the thermal infrared band and five pollutant parameters, i.e. Sulphur Dioxide (SO2), Nitrogen Dioxide (NO2), Carbon Monoxide (CO2), Ozone (O3) and Particulate Matters (particles less than 10 micron in size - PM10). The study area for this research covers the whole of Klang Valley Region and part of Negeri Sembilan. A limited area, which covers only part of the Shah Alam city is used for micro scale study. Since there are limited numbers of CAQM stations available, the concept of “Virtual Stations” is introduced to densify these stations. Based on these stations, kriging interpolation method (available in the GIS software) is used to generate the pollutant maps of different pollutant parameters of the study area.